In hospital outcomes among diabetics undergoing transcarotid artery revascularisation vs transfemoral carotid artery stenting & carotid endarterectomy. (3rd October 2022) - Hasnie, A; Hasnie, A; Adefisoye, J; Magee, K; Allaqaband, S; Jan, M F; Bajwa, T K; Haddadian, B
Abstract: Background: Transcarotid artery revascularisation (TCAR) is a novel procedure to intervene on carotid artery stenosis. It has previously shown to have lower rates of periprocedural adverse events compared to transfemoral carotid artery stenting (TFCAS) and carotid endartectomy (CEA). To date, no study has examined outcomes among diabetics undergoing TCAR compared to TFCAS and CEA. Purpose: We sought to determine the rates of adverse periprocedural outcomes related to TCAR, TFCAS and CEA in diabetics. Methods: The Vascular Quality Initiative Database was queried for all patients from March 2009 to April 2021 for diabetic patients undergoing carotid artery revascularisation via TCAR, TFCAS or CEA. Baseline demographic information as well as periprocedural outcomes were obtained. Results: A total of 57, 716 diabetic patients underwent carotid artery revascularisation. Of these 11.3% underwent TCAR (n=6569), 8.1% (n=4703) underwent TFCAS, and 80.4% (n=46, 444) underwent CEA. 39% (n=22, 528) were female and 87.3% (n=50, 377) were white. Compared to TFCAS, TCAR demonstrated lower rates of stroke (1.6% vs 2.2%, p=0.026), stroke/transient ischemic attack (2.2% vs 3.0%, p<0.001), and death (0.4% vs 1.3%, p<0.001) but remained higher than CEA for both stroke (1.6% vs 1.3%), stroke/TIA (2.2% vs 1.9%) and death (0.4% vs 0.3%). Conclusions: TCAR appears to be a safe revascularisation procedure for carotid artery stenosis with lower rates of stroke, stroke/TIA, and death in diabetics compared to TFCAS. However, rates remain higher than CEA. TCAR may thus be a viable alternative in diabetics who otherwise would be poor candidates for revascularisation via CEA. Funding Acknowledgement: Type of funding sources: None.